Thinking Process Analysis (Assimilation, Accommodation, Abstraction) Mathematics Ability of Junior High School Students in terms of Learning Style - Susanti, Susanti; Utami, Fathia; Alkiram, Shaheb; Mubarrak, Muhammad Zaki (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The purpose of this research is to know the thinking processed of student’s mathematical literacy abilities in terms of auditory, visual and kinesthetic learning styles. This research is an exploratory study with a qualitative approach. This research was conducted in Junior High Schools classified as Excellent in Meulaboh Regency. The subjects in this study were students of class IX MTsN 3 Aceh Barat who had the high-level ability and were able to solve math literacy problems, besides the subject was also chosen based on learning styles. The results showed that there was no significant difference in students mathematical literacy thinking processes based on visual learning styles is the process of assimilation and abtarksi thinking. Subjects with auditory learning styles, the thought processes of accommodation and abstraction for the kinesthetic learning styles, the processes of thinking, assimilation and abstraction.